Synthesis of Novel Heterocyclic Imine Type UV Absorbers for Application on Cotton Based Textile Materials - Ocal, Nuket; Aker, Acelya; Ergindemir, Hikmet Nil; Hamitbeyli, Agamirze (HINDAWI LTD, 2016)
Novel Schiff bases with the potential to exhibit biologically active and UV absorption properties were synthesized. Their application on cotton based textile materials was performed and the UV protection factor (UPF) values and the antibacterial features of the treated fabrics were measured.
Keywords: SOLVENT-FREE SYNTHESIS; SCHIFF-BASES; DERIVATIVES; TRANSFORMATIONS; PROTECTION; EFFICIENT; CELLULOSE; Chemistry